2013
DOI: 10.1021/ja4009216
|View full text |Cite
|
Sign up to set email alerts
|

Selective Nucleic Acid Capture with Shielded Covalent Probes

Abstract: Nucleic acid probes are used for diverse applications in vitro, in situ, and in vivo. In any setting, their power is limited by imperfect selectivity (binding of undesired targets) and incomplete affinity (binding is reversible, and not all desired targets bound). These difficulties are fundamental, stemming from reliance on base pairing to provide both selectivity and affinity. Shielded covalent (SC) probes eliminate the longstanding trade-off between selectivity and durable target capture, achieving selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…To further characterize the binding of Pu27 to its target sequence and determine the mechanism by which this binding could alter c-MYC transcription, we took advantage of a UV activated cross-linker to covalently bind the DNA target sequence and the Pu27 encoding oligonucleotide [ 45 ]. The cross-linker [3-cyanovinylcarbazole ( CNV K = K)] is a photoactive nucleoside analogue originally described by Yoshimura et.al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further characterize the binding of Pu27 to its target sequence and determine the mechanism by which this binding could alter c-MYC transcription, we took advantage of a UV activated cross-linker to covalently bind the DNA target sequence and the Pu27 encoding oligonucleotide [ 45 ]. The cross-linker [3-cyanovinylcarbazole ( CNV K = K)] is a photoactive nucleoside analogue originally described by Yoshimura et.al.…”
Section: Resultsmentioning
confidence: 99%
“…Pierce] that was incorporated at the position 1 = PuK1 or position 12 = PuK12 of the Pu27 nucleotide sequence (PuK1 and PuK12 were synthetized by IDT). The cross-linking protocol follows the methodology described by Dr. Pierce [ 45 ] with some modifications. The target sequences (1.8μM) were mixed or not with Pu27, PuK1 or PuK12 (3μM) in SSC buffer (150mM NaCl, 15mM trisodium citrate, pH7.0) and annealed for 5min at 95°C in heating block.…”
Section: Methodsmentioning
confidence: 99%
“…In a more recent work by Zhang et al. , the theoretical DF for C:C mismatch was calculated to be >10 000 (23). However, the reported experimental results were far below this value.…”
Section: Discussionmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) are the most common genetic variation in the human genome . DNA nanostructrues have recently been developed for highly specific detection of SNPs . Chen et al reported one such example based on conditionally fluorescent molecular probes ( Figure a).…”
Section: Nucleic Acids Detection and Genotypingmentioning
confidence: 99%